Premature placenta abruption: is there any alternative treatment in the IInd trimester of pregnancy? - Raba, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2010)
Objective : To present an original therapeutic method for placental abruption in the second trimester of gestation using hysterotomy with evacuation of a deciduous-placental haematoma. Material : Two pregnant women with placental abruption requiring delivery (24th and 23rd week of gestation, respectively). Method : Incision of the uterus with evacuation of a deciduous-placental haematoma. Results : Intrauterine continuation of pregnancy until maturity of the foetuses. Conclusion : Hysterotomy with evacuation of a deciduous-placental haematoma made it possible to continue pregnancy and avoid the necessity of immediate delivery by caesarean section.